1952
DOI: 10.1111/j.1744-6570.1952.tb01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Should Attitude Questionnaires Be Signed?

Abstract: THE following article presents the details of a study which attempted to investigate differences in responses to a pencil and paper questionnaire administered to two groups of individuals. In one group the respondents remained anonymous while in the second, respondents were identified. Three conclusions were reached. (1) Essentially the same responses were obtained for individuals in the group whether identified or anonymous. (2) Mean scores for the groups did not differ significantly.(3) These results may hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1955
1955
1986
1986

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…While it generally has been assumed that respondents are less likely to fake good when responding anonymously, previous research using personality inventories and attitude questionnaires has revealed small or no dif-ferences in the response given by subjects under anonymous and under identified conditions. This finding is consistent for research in which the same individuals have been tested under both anonymous and identified conditions (Corey, 1937;Fischer, 1946;Gerberich & Mason, 1948;Olson, 1936) and when equivalent groups have been tested (Ash & Abramson, 19S2;Hamel & Reif, 1952;Kosen, Kitchen, Kochen, & Stodolosky, 1970;Rosen, 1960).…”
Section: Effect Of Anonymity On Return Rate and Response Bias In A Ma...supporting
confidence: 76%
“…While it generally has been assumed that respondents are less likely to fake good when responding anonymously, previous research using personality inventories and attitude questionnaires has revealed small or no dif-ferences in the response given by subjects under anonymous and under identified conditions. This finding is consistent for research in which the same individuals have been tested under both anonymous and identified conditions (Corey, 1937;Fischer, 1946;Gerberich & Mason, 1948;Olson, 1936) and when equivalent groups have been tested (Ash & Abramson, 19S2;Hamel & Reif, 1952;Kosen, Kitchen, Kochen, & Stodolosky, 1970;Rosen, 1960).…”
Section: Effect Of Anonymity On Return Rate and Response Bias In A Ma...supporting
confidence: 76%
“…We have located seven studies in industrial settings which bear upon the question of the influence of anonymity upon morale or job satisfaction (3,14,17,24,29,45,58). Two studies from the Survey Research Center, University of Michigan, compare responses made by employees to morale items when the items are contained in an anonymous questionnaire and when they are part of an interview.…”
Section: Samplingmentioning
confidence: 99%
“…Fuller (1974), however, concludes from her review of the literature that the risk of significant bias is relatively small. While a few researchers have found some systematic bias, others have not, even when the information is somewhat sensitive (see Fischer, 1946;Ash and Abramson, 1952;Hamel and Reif, 1952;Rosen, 1960;Backer and Bakal, 1970;Rosen et ai, 1970;Fuller, 1974). King (1970), for example, found no difference in admission of drug use, in return rate, or in response to attitudinal items in a mail survey of Dartmouth undergraduates, half of whom received questionnaires with identifying numbers, half of whom did not.…”
mentioning
confidence: 95%